MICROPLASTICS: FORMATION, DISPOSITION, AND ASSOCIATED DANGERS. AN OVERVIEW. - Francisca Aranda; Bernabe L Rivas (Journal of the Chilean Chemical Society, 2023)
In recent decades the increase in the use of plastics has been exponential around the world, reaching a presence in places such as rivers, oceans and lakes, as well as in terrestrial environments such as agricultural soils. Associated with the great use of plastics in all areas of work, plastic particles smaller than 5 mm, called microplastics, have been found in all environmental matrices: aquatic environment, dispersed throughout the water column, terrestrial environment, infiltrating the soil sedimenting, and in the air, being transported by the wind. In each of these matrices, microplastic serves as transport for highly polluting compounds such as heavy metals, polycyclic aromatic hydrocarbons and organochlorine pesticides. In addition to environmental matrices, microplastics have been found in animals and humans in alarming numbers. In this way, this review addresses issues related to the formation and distribution of microplastics throughout the ecosystem and different organisms.